Phosphate dynamics and its fixation in different forms in acid sulfate, iron, toxic and neutral soils - Sovyanhadi, Yoedono (Iloilo College of Fisheries, University of the Philippines in the Visayas, 1985)
A study on dynamics of phosphate in acidic (acid sulfate and iron toxic) and neutral soils was conducted at the Brackishwater Aquaculture Center (BAC) of the University of the Philippines in the Visayas, College of fisheries in Leganes-Iloilo, from February to October 1984. The main objective of this study was to trace the mechanism of phosphate fixation and trend of its availability in these soils. The experiment was conducted in a Randomized Complete Block Design with 5 replicates of each treatment. The treatments were : Treatment A : unreclaimed acid sulfate soil, without phosphate application. Treatment B : unreclaimed acid sulfate soil ; with phosphate application ; Treatment C : lied acid sulfate soil, with phosphate application ; Treatment D : leached acid sulfate soil, with phosphate application ; Treatment E : neutral soil, with phosphate application ; Treatment F : iron toxic soil, with phosphate application. Superphosphate (0-18-0) at the rate of 50 kg/ha was twice, at an interval of 2 weeks, applied in all treatments except treatment A (control). Soil and water samples were collected during both application periods, everyday for the first week and once in the second week after P application. Soil samples were analyzed for total-P, the inorganic-P fractions (aluminum-phosphate, iron-phosphate and calcium-phosphate), available-P, exchangeable-A1 and Ca, active-iron, organic matter content, and wet and dry ph. The water samples were analyzed for total-P, soluble inorganic-P, soluble Ai, Fe and Ca, pH, alkalinity, dissolve oxygen, slinity and temperature. The amounts of phosphate found in various forms in different treatments were compared by using same units of measurement for any given time and for overall values with time. Phosphate-use efficiency was calculated as the ratio of phosphate utilized by growing organisms (plankton/lumut/lab-lab) and the amount of added phosphate. The productivity of the sols was determined by measuring the dry weight of plankton per unit volume (liter) of water and ash-free dry weight of lumut and/or lab-lab per unit (m2) surface area. The results of the study indicate taht majority of the supplied-P was fixed in all soils tested. The magnitude of fixation was A1-phosphate (30.5%), Ca-phosphate (30.0%) and Fe-phosphate (15.4%) in acid sulfate ; A1-phosphate (47.2%), Fe-phosphate (27.3% and Ca-phosphate (2.4% in iron toxic ; and Ca-phosphate (79.9%), Fe-phosphate (8.6%) and A1-phosphate (0.3% in neutral soils. The P-use efficiency in general was 1.11% in neutral soil, 0.14% in acid sulfate soil and 0.11% in iron toxic soil. The lime treated acid sulfate soil had better P-use and less P fixation compared to the control. The soil without P application gave lowest amount of available-P and growth of organisms, thus reduce P-user and lowest soil productivity.
Thesis (M. S. Fisheries) -- Iloilo, Philippines : University of the Philippines in the Visayas, April 1985
Keywords: Phosphate dynamics; Acid sulfate soil; Toxicity